A Connected Mobility Scheme for Taxi Supply-Demand Balancing in a Smart City Context - Haddad, Hedi; Bouyahia, Zied; Horchani, Leila; Jabeur, Nafaa; Gharrad, Hana (COMPUTING AND INFORMATICS, 2022)
In this paper we present the preliminary results of simulation-based experiments of an integrated scheme that has been proposed to control taxi supply-demand imbalance in the context of a smart city with multiple taxi operators and using Connected Mobility. We particularly explore the difference between centralized and decentralized implementations of the scheme as well as between collaborative and competitive attitudes of connected taxis. Our results show that by sharing knowledge about supply-demand imbalance and adopting a collaborative attitude, connected taxi systems can improve the performance of the service across a city by achieving a better supply-demand service balancing while improving their profits.